Fast and facile synthesis of two-dimensional FeIII nanosheets based on fluid-shear exfoliation for highly catalytic glycolysis of poly(ethylene terephthalate). Issue 2 (17th November 2020) - Jeong, Jae-Min; Jin, Se Bin; Son, Seon Gyu; Suh, Hoyoung; Moon, Jong-Min; Choi, Bong Gill
Abstract : 2D Fe III nanosheets are synthesized by a fluid dynamics–assisted exfoliation and oxidation method for highly-catalyzed glycolysis reaction of PET. Abstract : In this study, two-dimensional (2D) and exfoliated Fe III nanosheets are prepared using a fast and facile fluid-dynamics-induced exfoliation method for large-scale production. The resulting Fe III nanosheet is ultrathin and of 2D morphology with a high surface area. The Fe III nanosheet exhibits excellent glycolysis-catalytic performance for polyethylene terephthalate (PET) degradation to produce a bis(hydroxyethyl) terephthalate (BHET) monomer. A high PET conversion of 100% and a high BHET yield of 100% using the Fe III nanosheet catalyst are achieved within a short reaction time (30 min) at a reaction temperature of 200 °C. Furthermore, the Fe III nanosheet catalyst shows excellent recyclability for the glycolysis of PET, and a high BHET yield of 96.7% was obtained after five cycles.